Effect of Citrullus lanatus Seeds Extract on Haematological Parameters After Administration with Medroxyprogesterone Acetate on Female Wistar Rats - Nnumolu, Michael Chuks; Godspower, Onyeso (Biology, Medicine, & Natural Product Chemistry, 2023)
This study was carried out to investigate the effect of Citrullus lanatus seeds extract on the haematological parameters after administration with medroxyprogesterone acetate on female Wistar rats. Twenty-five rats weighing 170-230 g were divided into five groups containing five rats each. Group I served as control and received only rat chow and water; Group II received rat chow, water and a high dose of MPA only; Group III received rat chow, water, a high dose of MPA and a high dose of extract; group IV received rat chow, water, high dose of MPA and a low dose of extract, and group V received rat chow, water and high dose of extract only. The administration lasted for twenty-eight days after two weeks of acclimatisation. On the twenty-ninth day, the animals were anaesthetised using chloroform, sacrificed and their blood samples obtained via cardiac puncture for haematology analysis. The results showed that the level of haematological parameters significantly increased (p<0.05) in the rats that received a high dose of MPA and a high dose of Citrullus lanatus seed extract compared to the control group. This suggests that MPA affects bone marrow, which produces blood cells, significantly decreasing platelet count, white blood cell count, red blood cell count, haemoglobin count, packed cell volume, mean corpuscular volume, and mean corpuscular haemoglobin concentration. This study also shows that an aqueous extract of Citrullus lanatus seed is potent in increasing the level of haematological parameters when co-administered with MPA.